Full-Stokes polarization imaging based on liquid crystal variable retarders and metallic nanograting arrays. (18th October 2019) - Xu, Canhua; Ma, Jing; Ke, Chaozhen; Huang, Yantang; Zeng, Zhiping; Weng, Weixiang; Shen, Lituo; Wang, Kangjun
Abstract: A full-Stokes polarization imaging method was introduced by using a liquid crystal variable retarder (LCVR) and the metallic nanograting arrays. The linear polarization was detected based on the dichroic transmission of the metallic nanograting. The circular polarization was retrieved from two successive measurements with different retardance or orientation of LCVR. The determinant of data retrieve matrix was analyzed for the LCVR optimization. A full-Stokes imaging setup was built, calibrated, and proof-of-principle verified through imaging of radially polarized beams.